Phenotypic screens for SIRPA expression reveal RAB21 as a general regulator of macrophage surface identity - Adrian Granda Farias; Brian Feng; Shahbaz Khan; Wayne Ngo; Jamie L.Y. Wu; Magali Aguilera-Uribe; Shan Grewal; Patricia Mero; Sheila K. Singh; Thomas Kislinger; Warren C.W. Chan; Jason Moffat (Cell Reports, 2025)
Summary: Factors influencing the macrophage surfaceome define macrophage identity and behavior. Here, we use genome-wide phenotypic screens to identify genes affecting the accessibility and surface expression of macrophage signal regulatory protein alpha (SIRPA). Our data are consistent with previous evidence but also implicate glutaminyl-peptide cyclotransferase-like (QPCTL) in cis CD47-SIRPA interactions. We also identify endolysosomal factors encoded by Ras-associated binding protein 21 (RAB21) and members of the CCC (COMMD/CCDC22/CCDC93) and Wiskott-Aldrich syndrome protein and SCAR homolog (WASH) complexes as modulators of SIRPA expression. Surface immunophenotyping and surfaceome profiling show that inactivation of either Sirpa or Rab21 remodels cell surface protein expression. In contrast to Sirpa, Rab21 appears to be a general regulator of established macrophage cell surface markers. Perturbation of RAB21/Rab21 reduced Fc gamma receptor (FcγR) expression, leading to decreased uptake of antibody-nanoparticle conjugates and impaired phagocytosis of opsonized cells. To summarize, our study describes circuitry controlling SIRPA expression on macrophages and reveals a conserved RAB21-dependent trafficking pathway that has a role in modeling the cell surface of macrophages.